Curriculum innovation in the part-time madrasah learning system in Singapore - Sarkiman, Akhmudi; Zamsiswaya; Husti, Ilyas; Salman, Nola Fibriyani Bte (Program Studi Magister Pendidikan Agama Islam, 2025)
Singapore is a secular government system, where every policy does not include religious elements, including education. However, the Singapore government is quite responsive in providing support for the sustainability of Islamic educational activities. This study aims to analyze the management and curriculum of part-time madrassas and also find out how the role of part-time madrassas in equipping Muslim children of various ages with secular education to understand and practice Islam as a way of life especially in facing the challenges of the times. This study offers an overview and look at the management, curriculum and role of part-time madrasas in Singapore. Using a qualitative method that includes a literature review and field study, the research is a combination of object research conducted directly at the research site, combined with literature research. Data was obtained through interviews with several parties involved in part-time education as well as research papers related to the basics of Islamic education in Singapore either in the form of books or journal articles, as well as other documents. The results show that the Islamic Religious Council of Singapore (MUIS) plays a major role in monitoring and managing the development of Islamic education in Singapore. Since the Muslim community in Singapore needs to display progressive characteristics and have a vision of a model community that creates a distinctive Singaporean Islamic thought, MUIS introduced the aL.I.V.E (Learning Islamic Values Everyday) Program curriculum established through SIES (Singapore Islamic Education System) for part-time madrassas. Abstrak Singapura adalah sistem pemerintahan sekuler, di mana setiap kebijakan tidak memasukkan unsur agama, termasuk pendidikan. Namun, pemerintah Singapura cukup responsif dalam memberikan dukungan bagi keberlangsungan kegiatan pendidikan Islam. Penelitian ini bertujuan untuk menganalisis manajemen dan kurikulum madrasah paruh waktu dan juga mengetahui bagaimana peran madrasah paruh waktu dalam membekali anak-anak Muslim dari berbagai usia yang berpendidikan sekuler untuk memahami dan mengamalkan Islam sebagai pandangan hidup terutama dalam menghadapi tantangan zaman. Penelitian ini menawarkan gambaran dan melihat manajemen, kurikulum dan peran madrasah paruh waktu di Singapura. Dengan menggunakan metode kualitatif yang mencakup tinjauan literatur dan studi lapangan, dimana penelitian yang dilakukan merupakan gabungan antara penelitian obyek yang dilakukan secara langsung di lokasi penelitian, dipadukan dengan penelitian kepustakaan. Data diperoleh melalui wawancara dengan beberapa pihak yang terlibat dalam pendidikan paruh waktu serta penelitian makalah yang berkaitan dengan dasar-dasar pendidikan Islam di Singapura baik dalam bentuk buku atau artikel jurnal, serta dokumen lainnya. Hasil penelitian menunjukkan bahwa Majelis Ugama Islam Singapura (MUIS) berperan besar dalam memantau dan mengelola perkembangan pendidikan Islam di Singapura. Karena komunitas Muslim di Singapura perlu menampilkan karakteristik progresif dan memiliki visi model komunitas yang menciptakan pemikiran Islam khas Singapura, MUIS memperkenalkan kurikulum Program aL.I.V.E (Learning Islamic Values Everyday) yang dibentuk melalui SIES (Singapore Islamic Education System) untuk madrasah paruh waktu.